597 Sleep Bruxism in Preschool Children: Associations with Emotional-Behavioral Problems. (3rd May 2021) - Laganière, Christine; Kenny, Samantha; Gaudreau, Hélène; Pokhvisneva, Irina; Bouvette-Turcot, Andrée-Anne; Meaney, Michael; Pennestri, Marie-Helene
Abstract: Introduction: Several psychosocial factors contribute to the etiology of sleep bruxism in childhood, including emotional-behavioral problems, as well as environmental and familial factors. It is known that sleep bruxism is prevalent in preschoolers, but most etiology studies were conducted with school-aged children or adolescents. Studies focusing on younger, preschool-aged populations that consider family-related factors are lacking. This study aimed to assess the relationship between emotional-behavioral problems and the presence of sleep bruxism in preschoolers, while taking maternal depressive symptoms into consideration. Methods: Three hundred eighty-three mother-child dyads from the Maternal Adversity, Vulnerability, and Neurodevelopment (MAVAN) cohort were included in the present study. Mothers completed the Child's Sleep Habits Questionnaires (CSHQ; includes the frequency of bruxism), a questionnaire about their child's emotional-behavioral problems (CBCL; anxiety and depressive problems), and reported their own depressive symptoms (CES-D). Measures were completed at two timepoints: when children were 4 and 5 years old. Generalized Estimating Equation (GEE) models were used to evaluate the relationship between sleep bruxism frequency and children's emotional-behavioral problems, while controlling for maternal depressive symptoms, child's biological sex, family socioeconomic status, and age. Results: Maternal reports indicated that 12% of children experienced sleep bruxism at least sometimes at age four, and 20% did at age five. Children's anxiety and depressive symptoms were associated with increased sleep bruxism frequency (p < 0.05). Associations between children's emotional-behavioral problems and bruxism remained statistically significant when controlling for maternal depressive symptoms, child's biological sex, family socioeconomic status, and time (p < 0.05). Conclusion: In this normative cohort of children, sleep bruxism was associated with anxiety and depressive symptoms in children as young as age four. Furthermore, this relationship can still be observed when the severity of maternal depressive symptoms is considered. Whether anxiety and depressive symptoms contribute to sleep bruxism, or vice versa, remain to be further investigated. Nevertheless, results suggest that screening of emotional-behavioral problems should be considered in children experiencing sleep bruxism. Support (if any): Fonds de recherche du Québec - Santé